Exploratory Study of Flexural Performance of Mechanically Recycled Glass Fiber Reinforced Polymer Shreds as Reinforcement in Cement Mortar. Issue 10 (October 2021) - Haider, Md Mostofa; Nassiri, Somayeh; Englund, Karl; Li, Hui; Chen, Zhen
Millions of tons of glass fiber reinforced polymer (GFRP) waste have been steadily generated from end-of-life wind turbine blades and many other GFRP composites prevalent in everyday life, with limited reuse options. Recycled GFRP (rGFRP) by mechanical processing could be used in mortar and concrete as fibers or fillers. Maintaining the composite nature of rGFRP with a high fiber content is paramount to increased mechanical properties for concrete. In this study, high-modulus rGFRP particles were produced in three small, medium, and large relative sizes by hammer milling and screening. Small and medium rGFRPs were used in 1, 2, 3%, and large rGFRP in 1, 2, 3, 5, and 7% volume replacing sand in mortar. Almost all rGFRP-mortars showed significant improvement in flexural strength with their high modulus. All size groups of rGFRP progressively showed higher fracture toughness at higher amounts. Within the large group, 5 and 7%Vol had flexural toughness of about 2.00J compared with 0.75J of 3%Vol. Large rGFRP at 5 and 7%Vol offered nearly 60% and 70% 28 day equivalent flexural ratio. Micrographs of rGFRP–matrix interfaces from fracture faces showed rGFRP was well embedded within the matrix, provided bridging and deflecting of microcracks, and failed in pullout or rupture modes. Fly ash and silica fume had a positive synergy with 3%Vol large rGFRP and improved its flexural toughness from 0.75J to 1.12 and 1.00J, respectively. The investigated recycling process and sizes of rGFRP shreds showed great promise in this exploratory study and are recommended for further evaluation for highway and bridge concrete.